Visual communication and social networks for tourism development of the rural communities of the province of Guayas - Fatuly Addum, Saadda; Herrera Rivas, Keila; Vilema Herrera, Keila (Conexiones UG, 2024)
The study is the result of a research project called “Interdisciplinary approach to the tourist development of rural communities in the province of Guayas”, whose objective is to strengthen tourist destinations in rural Ecuador, focusing on the Ecuadorian coast. For this reason, a descriptive research is applied, with an ethnographic method, where as a first phase the social reality of the cocoa producing organizations of Fino Aroma is analyzed, who have begun to offer rural tourism. From the communication point of view, an empirical management is identified, with an initial diagnosis on the strategies of diffusion and commercialization of their products. A bibliographical review is conducted and the communication factors and strategies that influence promotion and positioning are determined. As a result, proposals designed by students from the University of Guayaquil are presented, within the framework of the graduation process. The approach to local culture is observed for the design and renewal of the image of microenterprises, with an innovative approach, under the parameters of visual communication and the point of view of the leaders of the organizations. Finally, the role of social networks as a new promotion channel is reflected upon, as is the importance of adapting to new changes, given that cyberspace is a reality for all productive sectors. At the same time, the participation of the academy is highlighted, with the research area, to contribute to society with knowledge.